Development of a high-speed, phase-sensitive laser probe system for RF surface acoustic wave/bulk acoustic wave devices with an absolute vibration amplitude measurement function. (20th April 2021) - Takahashi, Hikaru; Omori, Tatsuya; Hashimoto, Ken-ya
Abstract: This paper describes the coaxial integration of a Michelson interferometer (MI) and a Sagnac interferometer (SI) in a high-speed, phase-sensitive laser probe for surface acoustic wave/bulk acoustic wave devices. This combination enables the MI to be used for calibration of the vibration amplitude captured by the SI without sacrificing the measurement accuracy and speed of the SI-based laser probe. First, the system setup is detailed. Next, simultaneous measurement is performed using the SI and MI, and good coincidence is demonstrated between these measured results after correction of tiny misalignment between two optical axes. This means that the calibration can be performed simply by multiplying the data captured by SI by a coefficient of proportionality; this value of this can be determined by comparison with the data captured by simultaneous measurement for a tiny area. Finally, the procedure for absolute vibration amplitude measurement is proposed and its validity is confirmed by actual measurement.